Audience Reception Analysis on the Phenomenon of ‘Nonsense’ Lyrical Meaning of Asmalibrasi by Soegi Bornean (Universitas Negeri Semarang, 2023)
This article discusses the prevailing debate regarding the phenomenon of ‘nonsense’ lyrical meaning of Asmalibrasi, a song released in 2020 by Soegi Bornean, in the scope of audience reception analysis. The analysis focuses on how the audiences interpret the process of meaning making and how they perceive the aesthetic of the song amidts the backlash to its lyrical meaning which is deemed as meaningless and nonsense. This research used qualitative approach and collected the data through semi-structured interview and virtual observation. The data are the combination of primary data collected from semi-structured interview and virtual observation on twitter and secondary data gathered from online news and online articles. The discussion of the audience’s reception is based on encoding and decoding model by Stuart Hall to analyse the audience responses. Furthermore, the overall findings were synthesized and analysed according to the concept of characteristic and aesthetic of postmodern artworks, music, by Jameson. From the study, it is shown that the aesthetic of the song Asmalibrasi is not predefined and subject to fixed perception. It is rather more varied according to the listener’s individual perception. Moreover, the song Asmalibrasi maintains its aesthetic through emanating a vibe. The vibe emanated by Asmalibrasi is also what matters for the song to be enjoyed by the listeners. In other words, listeners have their personal perspective and consideration aspects in decoding the meaning which further define how they perceive the aesthetic of the song.